PENGELOLAAN DANA PENSIUN LEMBAGA KEUANGAN PT BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN - Muhammad Daifa Al Quthni (2021)
A pension fund program aimed at the public or employees in a company is certainly very useful as a guarantee in old age, it provides a sense of security because they receive benefits from pension funds. Thus, the pension benefits that will be received by participants are important things that must be managed properly and implemented with the applicable rules and regulations. PT. Bank Pembangunan Daerah Jawa Barat dan Banten or commonly known as Bank BJB has a pension fund business activity, namely the Financial Institution Pension Fund commonly called BJB DPLK organizes a defined contribution pension program whose management has implemented the principles of Good Pension Funds Governance including applying the principles of independence, transparency, accountability , accountability, and fairness. The purpose of this final report is to find out the proper management of Financial Institution Pension Funds in accordance with the regulations and principles of pension fund governance. The sources of discussion of the Final Project report used are books and interviews. The results of the Final Project report obtained are that the management of Financial Institution Pension Funds is carried out in a clear and structured manner in terms of management and distribution of investment funds. Keywords: Management, Financial Institution Pension Fund, PT Pembangunan Daerah Jawa Barat and Banten.